Peran Digital Marketing Terhadap UMKM Kopi Onthel Di Kota Tanjungpinang: Penelitian - Afriyadi; Ade Wahyudi Sihombing; Anggit Vellyana Putri; Anrias Oto; Denanto; Diva Buanaria; Farradina Nur Fitriazizah; Muhammad Redha Andrean; Riko Apriadi Nurdeni; Saskia Nabilla (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Digital transformation pushes small businesses to use social media as an affordable and effective marketing tool. The case of Kopi Onthel in Tanjungpinang shows that Instagram, TikTok, and WhatsApp help expand its market reach, strengthen brand identity, and boost customer engagement. Using a qualitative approach with interviews, observation, and documentation, the study finds clear impacts on customer visits, a broader consumer base, and stronger loyalty built through digital communities. Cost efficiency and user generated content add to these benefits, while visual identity and local storytelling improve competitiveness. Challenges remain, mainly inconsistent posting and limited use of analytics. Overall, digital marketing supports Kopi Onthel’s economic performance and local MSME growth, making consistent content, better analytics, and community collaboration increasingly important.